HUKUM MENYUAP DENGAN ALASAN DARURAT DALAM PEMILIHAN LEGISLATIF MENURUT TINJAUAN KAIDAH الضرورة تبيح المحظورات - Wahid Cahyono, Anang (Penerbit Lafadz Jaya, 2025)
The election of legislative candidates is one of the very important democratic practices in this beloved country. Of course not, because from this election people's representatives will be elected who will convey the aspirations of all Indonesian people based on their respective electoral districts. They are representatives of the people's wishes because in a democratic system, power is in the hands of the people. However, dirty practices in legislative elections have tarnished the good name of democracy in Indonesia. The practice of bribery (risywah) is something that is very worrying. For various reasons, including one of which is the emergency reason (al-dharurah) which is often used to legalize the practice. The reason for the concern that the people's representative council will be occupied by incompetent people according to some of them is the emergency conditions that allow for giving bribes to prospective voters. This study aims to identify the extent of the potential for emergencies that occur so that it can formulate a prohibition law or the existence of rukhsoh (leniency) in the practice of risywah in the election of legislative candidates by reviewing the rule